The Rise, Fall, and Resurgence of Modernization Theory - Karimi, Sirvan (Technium Social Sciences Journal, 2026)
Out of the intellectual fermentation of the post-World War II era, modernization theory emerged as a pervasive theoretical force to exercise a spectacular hegemony for three consecutive decades. The enchanting appeal of modernization theory emanated from its theoretical claim to have discovered an emancipatory formula that could allegedly extricate economically backward nations from the gravitational force of underdevelopment. Despite the ubiquity of the concepts of modernity and progress in socio-economic discourse, which is an indication of the continuing influence of modernization theory, the strength of modernization theory began to dwindle by the 1980s. It will be demonstrated that modernization theory was based on structural functionalism, which itself had been shaped by the Eurocentric assumptions of historical transformation. With the emergence of economic crises in the 1970s, which contradicted the theoretical foundations of modernization theory, the edifice of both structural functionalism and modernization theory began to crumble. Despite the eclipse of modernization theory’s appeal, its modified versions continue to be used by students of democratization and economic development.